Synthesis of La0.7Sr0.3MnO3 at 800 degrees C using citrate gel method - Ravi, V.; Kulkarni, S. D.; Samuel, V.; Kale, Sangeeta N.; Mona, J.; Rajgopal, R.; Daundkar, A.; Lahoti, P. S.; Joshi, Rakesh S. (Ceramics International, 2007)
Manganite systems have been of considerable interest in the recent past due to their potential to operate in wide property range and also to serve as effective magnetic sensing and storing devices when synthesized using stringent conditions. We report a novel citrate gel method, in which La0.7Sr0.3MnO3 system has been synthesized at temperature 800 degrees C (LSMO800) with the synthesis duration is 6 h. The results have been compared with the sample synthesized at 1050 degrees C (LSMO1050). The synthesized bulk polycrystalline sample shows single-phase nature with the increase in particle size from similar to 50 nm to 300 nm with the increase in the sintering temperature. The magnetization data for LSMO800 shows well-defined hysteresis with saturation magnetization at around 1800 Oe and Curie temperature at 360 K, which is slightly lower than that of LSMO1050, which is 375 K. The results can be well attributed to the grain boundary effects. (C) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Citrate gel method; CMR; Oxides

Structural-functional insights of single and multi-domain capsicum annuum protease inhibitors - Mishra, Manasi; Joshi, Rakesh S.; Gaikwad, Sushama M.; Gupta, Vidya S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2013)
Pin-II protease inhibitors (PIs) are the focus of research interest because of their large structural-functional diversity and relevance in plant defense. Two representative Capsicum annuum PI genes (CanPI-15 and -7) comprising one and four inhibitory repeat domains, respectively, were expressed and recombinant proteins were characterized. beta-Sheet and unordered structure was found predominant in CanPI-15 while -7 also displayed the signatures of polyproline fold, as revealed by circular dichroism studies. Inhibition kinetics against bovine typsin indicated three times higher potency of CanPI-7 (K-i similar to 57 mu M) than -15 (similar to 184 mu M). Activity and structural stability of these CanPIs were revealed under various conditions of pH, temperature and denaturing agent. Structure prediction, docking studies with proteases and mass spectroscopy revealed the organization of multiple reactive site loops of multi domain PIs in space as well as the steric hindrances imposed while binding to proteases due to their close proximity. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: CanPI; Circular dichroism; Disulfide bonding; Potato type-II protease inhibitors; Protein stability

Structural features of diverse Pin-II proteinase inhibitor genes from capsicum annuum - Mahajan, Neha S.; Dewangan, Veena; Lomate, Purushottam R.; Joshi, Rakesh S.; Mishra, Manasi; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
The proteinase inhibitor (PI) genes from Capsicum annuum were characterized with respect to their UTR, introns and promoter elements. The occurrence of PIs with circularly permuted domain organization was evident. Several potato inhibitor II (Pin-II) type proteinase inhibitor (PI) genes have been analyzed from Capsicum annuum (L.) with respect to their differential expression during plant defense response. However, complete gene characterization of any of these C. annuum PIs (CanPIs) has not been carried out so far. Complete gene architectures of a previously identified CanPI-7 (Beads-on-string, Type A) and a member of newly isolated Bracelet type B, CanPI-69 are reported in this study. The 5' UTR (untranslated region), 3'UTR, and intronic sequences of both the CanPI genes were obtained. The genomic sequence of CanPI-7 exhibited, exon 1 (49 base pair, bp) and exon 2 (740 bp) interrupted by a 294-bp long type I intron. We noted the occurrence of three multi-domain PIs (CanPI-69, 70, 71) with circularly permuted domain organization. CanPI-69 was found to possess exon 1 (49 bp), exon 2 (551 bp) and a 584-bp long type I intron. The upstream sequence analysis of CanPI-7 and CanPI-69 predicted various transcription factor-binding sites including TATA and CAAT boxes, hormone-responsive elements (ABRELATERD1, DOFCOREZM, ERELEE4), and a defense-responsive element (WRKY71OS). Binding of transcription factors such as zinc finger motif MADS-box and MYB to the promoter regions was confirmed using electrophoretic mobility shift assay followed by mass spectrometric identification. The 3' UTR analysis for 25 CanPI genes revealed unique/distinct 3' UTR sequence for each gene. Structures of three domain CanPIs of type A and B were predicted and further analyzed for their attributes. This investigation of CanPI gene architecture will enable the better understanding of the genetic elements present in CanPIs.
Keywords: CanPI; Capsicum; Gene architecture; Promoter; Proteinase inhibitor

Sequence characterization and in silico structure prediction of fatty acid desaturases in linseed varieties with differential fatty acid composition - Rajwade, Ashwini V.; Joshi, Rakesh S.; Kadoo, Narendra Y.; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2016)
BACKGROUND: Linseed is the richest agricultural source of alpha-linolenic acid (ALA), an omega-3 fatty acid (FA) that offers several nutritional benefits. In the present study, sequence characterization of six desaturase genes (SAD1, SAD2, FAD2, FAD2-2, FAD3A and FAD3B) and 3D structure prediction of their proteins from ten Indian linseed varieties differing in ALA content were performed to determine whether the nucleotide and amino acid (AA) sequence variants have any functional implications in differential accumulation of ALA or other FAs in linseed. RESULTS: The SAD and FAD2 genes exhibited few sequence variations among the ten varieties, forming only one or two protein isoforms. In contrast, the FAD3A and FAD3B genes showed more sequence variations and three or four protein isoforms. Interestingly, the two high-ALA varieties NL260 and Padmini had the same FAD3B nucleotide and protein isoforms, which differed from all other varieties. Surprisingly, no AA changes altered the 3D structures of the desaturase proteins. CONCLUSION: Several nucleotide and AA sequence variations in desaturase genes were observed; however, they did not alter the 3D structure of any desaturase protein and were not correlated with FA levels among the ten linseed varieties, which had different ALA contents. This suggests a complex regulatory process of biosynthesis of FAs in linseed. (C) 2016 Society of Chemical Industry